Circular economy as an approach to corporate social responsibility: a semi-systematic review (Gestión y Gerencia, 2022)
The circular economy is assumed as a paradigm of sustainability, which makes room for alternative models of business innovation focused on mastering the effective use of resources in scenarios of environmental, economic and social significance, implied in social responsibility. This article followed a systematic review of the literature, aimed at knowing: What is the state of knowledge about the circular economy as an approach towards corporate social responsibility? The theoretical deployment was structured from the categories: notions associated with the circular economy in business, elements of social responsibility from the circular economy, sustainability prospects around the circular economy. The methodology followed the planning, implementation and reporting phases. Among the findings, the macro concepts built on the basis of semantic complementarity were identified. The conclusions point to the priority of making decisions about productive practices in the performance of organizations that comply with environmental certifications, in accordance with global compacts. This will attract new research, by indicating the construction paths, which cannot be postponed to travel from the present to the future, by exploring business models based on the circular economy as an approach to social responsibility.
Keywords: Circular Economy; Efficiency; Management; Social Responsibility; Sustainability